2016
DOI: 10.1039/c6ra11744a
|View full text |Cite
|
Sign up to set email alerts
|

Structure and electrical properties of lead-free Bi0.5Na0.5TiO3-based ceramics for energy-storage applications

Abstract: optimum energy-storage properties were obtained in 0.90(BNT-BT)-0.10NT with energy-storage density of 1.2 J/cm 3 and energy-storage efficiency of 74.8% at 10 kV/mm. The results demonstrate that (1 -x)(BNT-BT)-xNT ceramics are promising candidate for high-temperature energy-storage application. IntroductionCapacitors play an important role in energy-storage system. Compared to batteries, capacitors possess faster charge-discharge time and higher power density [1,2]. However, the energy that capacitor dielectric… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
59
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 151 publications
(65 citation statements)
references
References 68 publications
(48 reference statements)
4
59
0
Order By: Relevance
“…It can be found that the first dielectric constant anomaly peak shifts to lower temperature and the magnitude of the anomaly peak decreases with increasing the value of x. It is due to the fact that large differences of ion valences and sizes among Ti 4+ , Zr 4+ and Nb 5+ in B-sites disturb the long range ferroelectric order of ceramics 10, 53, 54 . The second dielectric constant anomaly peak also decreases in magnitude while its position remains almost unchanged.…”
Section: Resultsmentioning
confidence: 96%
See 4 more Smart Citations
“…It can be found that the first dielectric constant anomaly peak shifts to lower temperature and the magnitude of the anomaly peak decreases with increasing the value of x. It is due to the fact that large differences of ion valences and sizes among Ti 4+ , Zr 4+ and Nb 5+ in B-sites disturb the long range ferroelectric order of ceramics 10, 53, 54 . The second dielectric constant anomaly peak also decreases in magnitude while its position remains almost unchanged.…”
Section: Resultsmentioning
confidence: 96%
“…The first dielectric anomaly is located at a low temperature of ~170 °C (Fig. 3 (c)) and shows an obvious frequency dispersion, which is caused by the thermal evolution of R3c and P4bm PNRs coexisted in a wide temperature range for BNT-based ceramics 10, 47, 50 . The second dielectric constant anomaly is located at a higher temperature of ~360 °C (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations